Heterotopic digital replantation for restoring hand function - Zamora, Juan Carlos García (International Surgery Journal, 2025)
Heterotopic digital replantation is a specialized reconstructive microsurgical technique used when an amputated digit cannot be replanted to its original site due to extensive local damage or multiple amputations. Instead, the viable digit is transferred to a non-anatomic position-most often to reconstruct the thumb or restore opposition-aiming to maximize functional outcome rather than anatomic accuracy. This approach is particularly indicated in cases of irreparable thumb loss, multiple non-replantable digits, or severe joint destruction where restoring prehension is the primary goal. The procedure requires precise microsurgical anastomosis of vessels and nerves and may be combined with free tissue or joint transfers. Reported outcomes show satisfactory sensory recovery, range of motion, and grip strength when careful surgical planning and rehabilitation are applied. However, potential complications include vascular thrombosis, infection, wound healing disorders, and long-term stiffness or sensory deficits. Despite these challenges, heterotopic replantation remains a valuable option for restoring meaningful hand function in complex injuries where traditional replantation is not feasible.